Guar, jantar, wheat straw, and rice hull composts as replacements for peat in muskmelon transplant production - Ghulam Mustafa; Muhammad Arif Ali; Donald Smith; Timothy Schwinghamer; John R. Lamont; Niaz Ahmed; Sajjad Hussain; Muhammad Arshad (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The demand for soilless media for vegetable transplant production is increasing. Economic constraints paired with concerns over the sustainability of peat mining have necessitated the replacement of peat with renewable and regionally abundant alternatives. The aim of this study was to develop from composts complete or partial substitutes for peat. Methods Composted guar (Cyamopsis tetragonoloba), jantar (Sesbania aculeata), wheat (Triticum aestivum) straw, and rice (Oryza sativa) hulls adjusted to 10% airfilled porosity (AFP) were blended on a volumetric basis with peat moss at discrete levels (0â50%). Total waterholding capacity, shrinkage, dry and wet bulk density, pH, electrical conductivity, N, P, K, FE, B, and Zn concentrations of each compost, their blends, and a peat control were measured. The experimental media were used to grow muskmelon (Cucumis melo) plants in a greenhouse. Seed germination, shoot fresh weight, shoot height, leaf area, stem diameter, root length, and mineral nutrient concentrations of transplants were quantified. After transplanting in the field, the growth rates and yields were measured. Nonparametric regression was used to analyze the data. Results The physiochemical parameters measured for most of the experimental media fell within the recommended range for growing media; however, pH for all media exceeded the recommended range. Media-containing guar and jantar composts generally contained more nutrients than media-containing rice hull or wheat straw composts. Fresh weight, height, and root length were generally greater for seedlings grown in media-containing rice hull compost than for those grown in media-containing other composts. Seedlings grown in media-containing guar or jantar composts generally had greater tissue nutrient concentrations. Conclusions All blends produced acceptable seedlings; however, the largest seedlings, and greatest post-transplant growth rate and yield were produced in media containing 30â50% rice hull compost.